IMPLEMENTASI MANAJEMEN BASIS DATA DALAM LINGKUP KECERDASAN BUATAN - Nayla Arnona Br Damanik; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the role of database management systems in supporting artificial intelligence (AI) performance for data-driven decision-making processes. The research method applies a literature review from relevant academic sources. The results show that the integration of AI and databases improves the accuracy, effectiveness, and efficiency of data processing, directly impacting decision-making quality. The conclusion highlights that intelligent database systems are a crucial foundation for AI implementation, although ethical and security challenges remain a significant concern for future development.